2022
DOI: 10.1186/s13287-022-02847-7
|View full text |Cite
|
Sign up to set email alerts
|

Function of epithelial stem cell in the repair of alveolar injury

Abstract: Alveoli are the functional units of blood-gas exchange in the lung and thus are constantly exposed to outside environments and frequently encounter pathogens, particles and other harmful substances. For example, the alveolar epithelium is one of the primary targets of the SARS-CoV-2 virus that causes COVID-19 lung disease. Therefore, it is essential to understand the cellular and molecular mechanisms by which the integrity of alveoli epithelial barrier is maintained. Alveolar epithelium comprises two cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Moreover, several signaling pathways promoting the transition of AECII to AECI have been elucidated. Recent characterisation of AECII-derived intermediate cells, emerging during reparative stages after bacteria-induced damage, identified distinct AECII subgroups, supporting the hypothesis of AECII differentiation towards AECI [86]. This intermediate state was characterised by the expression of keratin (Krt) 8, Cldn4, Ctgf, and Sfn [86].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Moreover, several signaling pathways promoting the transition of AECII to AECI have been elucidated. Recent characterisation of AECII-derived intermediate cells, emerging during reparative stages after bacteria-induced damage, identified distinct AECII subgroups, supporting the hypothesis of AECII differentiation towards AECI [86]. This intermediate state was characterised by the expression of keratin (Krt) 8, Cldn4, Ctgf, and Sfn [86].…”
Section: Discussionmentioning
confidence: 74%
“…Recent characterisation of AECII-derived intermediate cells, emerging during reparative stages after bacteria-induced damage, identified distinct AECII subgroups, supporting the hypothesis of AECII differentiation towards AECI [86]. This intermediate state was characterised by the expression of keratin (Krt) 8, Cldn4, Ctgf, and Sfn [86]. Studies have suggested the involvement of immune cells and inflammatory paracrine factors such as TNF-α and IL-1β in ACEII repair and transition into AECI [87,88].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…During the period of lung fibrosis, several intermediate AECII was detected by specific markers such as keratin 8 (KRT8), claudin 4 (CLDN4) and stratifin (SFN). When the alveolar repair failed due to repetitive injury, the progression of chronic lung diseases could be triggered [ 40 ]. It was demonstrated that radiation-induced AECII senescence participated in pulmonary fibrosis, and NADPH oxidase (NOX) and insulin-like growth factor-1 receptor (IGF-1R) were significantly involved in [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Diverse in vivo injury models of mice and in vitro 3D organoid culture models have revealed the transient AT2 cell subpopulations that appear in the middle of the transition from AT2 to AT1, named as "alveolar differentiation intermediate (ADI)," "pre-alveolar type-1 transitional cell state (PATS)," "damage-associated transitional progenitors (DATPs)," or "AT0" by different groups. 19,[21][22][23] The expression profiles of these cells are somewhat similar; for example, most of them express keratin 8 (Krt8), while some also express claudin 4 (Cldn4), keratin 19 (Krt19), connective tissue growth factor (Ctgf), and stratifin (Sfn). 22 AT2 cells in regenerating lung models transiently acquire an intermediate state from which they can differentiate into AT1 cells or terminal and respiratory bronchiole secretory cells.…”
Section: Alveolar Epithelial Cellsmentioning
confidence: 99%